The legacy of intensive agricultural history on the soil health of (sub)tropical landscapes - Crow, Susan E.; Hubanks, Hannah; Deenik, Jonathan L.; McClellan Maaz, Tai; Tallamy Glazer, Christine; Vizka, Elaine; Rivera-Zayas, Johanie (Frontiers in Environmental Science, 2023)
Soil health conceptualized as a measurable ecosystem property provides a powerful tool for monitoring progress in restoration projects or implementation of best management practices to improve degraded lands and promote sustainable agroecosystems. We surveyed soils collected from a range of land uses (i.e., protected native and non-native forest, managed pasture, unmanaged previously intensive agricultural lands, organic cropland, and conventional cropland) across a range of soil orders (Oxisol, Mollisol, Andisol, Inceptisol, and Vertisol) on three Hawaiian Islands. Forty-six soil health indicators encompassing biological, chemical, and physical properties were measured. In this multivariate survey, the most distinct group was the unmanaged, previously intensive agriculture lands, which was significantly different from all other land uses even when considering differences in mineralogy. Importantly, the soil health indicators of well-managed pastures in Hawaiʻi were not different from protected forests, suggesting that well-managed grazing lands may be as healthy and resilient as protected forests. A suite of 11 readily measured indicators emerged out of a first-principle approach to determining a holistic indication of soil health across a range of soils and systems in Hawaiʻi encompassing much of the diversity in the tropics and subtropics. Every land use may improve its soil health status within a reasonable range of expectations for a soil’s land use history, current land use, and mineralogy. Key drivers of inherent differences in the soil health indicators, including intensive land use history, current land use practices, and mineralogy, must be interwoven into the soil health index, which should set minimum and maximum benchmarks and weight indicators according to equitable standards.